PELATIHAN PEMBUATAN MULTIMEDIA AUDIO VISUAL BERBASIS ANDROID PADA TPA AL-IKHLAS - Fitri Fitri; Leonardo Kamajaya; Adi Candra Kusuma; Anindya Dwi Risdhayanti; Mohammad Luqman; Muhammad Khairuddin; Dinda Ayu Permatasari (P3M Politeknik Negeri Malang, 2024)
Moving sign musholla is very important as an interactive learning media for TPA children because the moving sign also contains information on the letters of the Al-Quran, in addition Quran murrotal audio to make children who recite the Quran can listen to the chanting of verses and can memorize these letters. In addition, this moving sign provides other information such as prayer time schedules, besides that it is also useful for the muezzin to know when to call to prayer and iqamah, while the benefit for the congregation is to know the prayer time when in the prayer room. Besides containing prayer times, hours and dates. The moving sign display as well as the addition of audio is more attractive to the atmosphere of the children in the TPA. Many musholla in Malang already have moving sign facilities, but there are some that still do not have moving sign facilities, one of which is TPA Musholla Al-Ikhlas.